Resin composition, cured product, laminate, transparent antenna, and image display device
By using a resin composition containing a styrene-based block copolymer and a (meth)acrylic compound, the wrinkle of conductive parts is suppressed, and the wrinkle problem during curing of the resin composition is solved, thereby achieving a high tensile elastic modulus and excellent mediation Electrical characteristics, suitable for transparent antennas for high-frequency communication.
Patent Information
- Application Number
- CN202380030667.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-10
- Filing Date
- 2023-03-29
- Publication Date
- 2025-01-10
AI Technical Summary
During the curing process of the resin composition, the conductive parts are prone to wrinkles, affecting the performance of the transparent antenna.
Using a resin composition containing a styrene-based block copolymer, a (meth)acrylic compound and a peroxide, a cured product with a high tensile elastic modulus was obtained by heat treatment at 120°C for 30 minutes, thereby suppressing the conducting member. wrinkle and improve the dielectric properties of transparent antennas.
Effectively suppresses wrinkles in conductive components, while providing excellent transparency and dielectric properties, and is suitable for high-frequency band communications of high-speed and large-capacity communications.
Smart Images

Figure BDA0005061400060000021 
Figure BDA0005061400060000121 
Figure BDA0005061400060000331
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition, a cured product, a laminate, a transparent antenna, an image display device, and the like. Background Art
[0002] The antenna for receiving radio waves is provided in an image display device (for example, an image display device in various electronic devices such as a personal computer, a navigation system, a mobile phone, a clock, an electronic dictionary, etc.), a component of a car, a building, etc. For example, an image display device with a built-in antenna is sometimes used. In recent years, in order to correspond to the miniaturization, thinning, and diversification of shapes of image display devices and ensure the likelihood of design, it has been proposed to configure a transparent and low-visibility antenna (hereinafter also referred to as a "transparent antenna") on the image display portion for displaying images. Various components have been studied for components for obtaining a transparent antenna (for example, refer to the following patent document 1).
[0003] Previous technical literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2011-091788 Summary of the invention
[0006] Technical issues to be solved by the invention
[0007] When obtaining a transparent antenna, a laminate having a cured product of a resin composition and a conductive component abutting the cured product is sometimes used. Such a laminate can be obtained by curing the resin composition in a state where the resin composition abuts against the conductive component. However, according to the present inventors' understanding, wrinkles are sometimes generated in the conductive component when the resin composition is cured, and it is required to suppress the generation of such wrinkles.
[0008] One aspect of the present invention is to provide a resin composition that can suppress the generation of wrinkles in a conductive component when the resin composition is cured in a state where the resin composition is in contact with the conductive component. Another aspect of the present invention is to provide a cured product of the resin composition. Another aspect of the present invention is to provide a laminate using the resin composition or its cured product. Another aspect of the present invention is to provide a transparent antenna using the cured product of the resin composition. Another aspect of the present invention is to provide an image display device using the transparent antenna.
[0009] Means for solving technical problems
[0010] The present invention is related to the following [1] to
[18] in several aspects.
[0011] [1] A resin composition comprising an elastomer, a polymerizable compound and a polymerization initiator, wherein the resin composition provides a cured product having a tensile elastic modulus of 50 MPa or more when heat treated at 120° C. for 30 minutes.
[0012] [2] The resin composition according to [1], wherein the elastomer comprises a styrene block copolymer.
[0013] [3] The resin composition according to [1] or [2], wherein the elastomer comprises a styrene-butadiene-styrene block copolymer.
[0014] [4] The resin composition according to any one of [1] to [3], wherein the content of the elastomer is 50% by mass or more based on the total mass of the resin composition.
[0015] [5] The resin composition according to any one of [1] to [4], wherein the polymerizable compound includes a (meth)acrylic compound.
[0016] [6] The resin composition according to any one of [1] to [5], wherein the polymerizable compound contains alkanediol di(meth)acrylate.
[0017] [7] The resin composition according to any one of [1] to [6], wherein the polymerizable compound includes a compound represented by the following general formula (I).
[0018]
[0019] [Where R 1 represents a group containing 9 or less carbon atoms and 2 or more oxygen atoms, R 2a and R 2b Each independently represents a hydrogen atom or a methyl group.]
[0020] [8] The resin composition according to any one of [1] to [7], wherein the polymerization initiator contains a peroxide.
[0021] [9] The resin composition according to any one of [1] to [8], wherein the polymerization initiator contains a peroxyester.
[0022]
[10] A cured product, which is a cured product of the resin composition according to any one of [1] to [9].
[0023]
[11] A laminate comprising a substrate film and a transparent resin layer disposed on the substrate film, wherein the transparent resin layer comprises at least one selected from the group consisting of the resin composition according to any one of [1] to [9] and a cured product thereof.
[0024]
[12] The laminate according to
[11] , further comprising a conductive member disposed on the transparent resin layer.
[0025]
[13] The laminate according to
[12] , wherein the conductive member contains copper.
[0026]
[14] The laminate according to
[12] or
[13] , wherein the thickness of the conductive member is 5 μm or less.
[0027]
[15] A transparent antenna comprising a transparent substrate, a conductive component disposed on the transparent substrate, and a covering component disposed on the conductive component, wherein at least one selected from the group consisting of the transparent substrate and the covering component comprises a cured product of the resin composition described in any one of [1] to [9].
[0028]
[16] The transparent antenna according to
[15] , wherein the conductive member has a mesh portion.
[0029]
[17] The transparent antenna according to
[15] or
[16] , wherein the conductive component contains copper.
[0030]
[18] An image display device comprising the transparent antenna described in any one of
[15] to
[17] .
[0031] Effects of the Invention
[0032] According to one aspect of the present invention, a resin composition can be provided that can suppress the generation of wrinkles in a conductive component when the resin composition is cured in a state where the resin composition is in contact with the conductive component. According to another aspect of the present invention, a cured product of the resin composition can be provided. According to another aspect of the present invention, a laminate using the resin composition or its cured product can be provided. According to another aspect of the present invention, a transparent antenna using the cured product of the resin composition can be provided. According to another aspect of the present invention, an image display device using the transparent antenna can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a schematic cross-sectional view showing an example of a laminated body.
[0034] Figure 2 It is a schematic cross-sectional view showing an example of a laminated body.
[0035] Figure 3 It is a schematic cross-sectional view showing an example of an image display device.
[0036] Figure 4 It is a schematic cross-sectional view showing an example of an image display device. DETAILED DESCRIPTION
[0037] Hereinafter, embodiments of the present invention will be described in detail. However, the present invention is not limited to the following embodiments.
[0038] In this specification, the numerical range shown by "~" indicates the range including the numerical values recorded before and after "~" as the minimum and maximum values, respectively. "Above A" in the numerical range refers to A and the range exceeding A. "Below A" in the numerical range refers to A and the range less than A. In the numerical range recorded in stages in this specification, the upper limit or lower limit of the numerical range of a certain stage can be arbitrarily combined with the upper limit or lower limit of the numerical range of other stages. In the numerical range recorded in this specification, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiment. "A or B" can include either A and B, or both. The materials exemplified in this specification are not particularly limited, and can be used alone or in combination of two or more. In this specification, with respect to the content of each component in the composition, when there are multiple substances that meet the various components in the composition, unless otherwise specified, it refers to the total amount of the multiple substances present in the composition. With respect to the term "layer", in addition to the structure of the shape formed on the entire surface when observed in a top view, it also includes the structure of the shape formed in a part. The term "process" includes independent processes, even if they cannot be clearly distinguished from other processes, as long as the intended effect of the process can be achieved. "(Meth)acrylate" refers to at least one of acrylate and its corresponding methacrylate. The same applies to other similar expressions such as "(meth)acrylic acid". The content of (meth)acrylic acid-based compounds refers to the total amount of acrylic acid-based compounds and methacrylic acid-based compounds. Hydroxyl groups do not include OH groups included in carboxyl groups.
[0039] The resin composition involved in the present embodiment contains an elastomer, a polymerizable compound and a polymerization initiator. In the resin composition involved in the present embodiment, when the resin composition is heat-treated at 120°C for 30 minutes, a cured product with a tensile elastic modulus of 50 MPa or more is provided. The resin composition involved in the present embodiment can be used as a resin composition for a transparent antenna. The resin composition involved in the present embodiment can be used as a thermosetting resin composition. The cured product involved in the present embodiment is obtained by curing the resin composition involved in the present embodiment, and is a cured product of the resin composition involved in the present embodiment. The cured product involved in the present embodiment can be in a semi-cured state or a fully cured state.
[0040] According to the resin composition involved in this embodiment, when the resin composition is cured in a state where the resin composition abuts against the conductive component, the generation of wrinkles in the conductive component can be suppressed. For example, when the resin composition is cured by heat treating the resin composition at 120°C for 30 minutes in a state where the resin composition abuts against the conductive component, the generation of wrinkles in the conductive component can be suppressed.
[0041] According to one aspect of the resin composition according to the present embodiment, as described above, a cured product having excellent transparency while suppressing the occurrence of wrinkles in the conductive member can be obtained.
[0042] Transparent antenna can be used in the communication of high frequency band for realizing high-speed and large-capacity communication. In the communication of high frequency band, there is a tendency that the transmission loss is large. Therefore, as a component of transparent antenna, the cured product of resin composition is required to have excellent dielectric properties. According to one mode of the resin composition involved in the present embodiment, a cured product with excellent relative dielectric constant (low relative dielectric constant) can be obtained. According to one mode of the resin composition involved in the present embodiment, in the evaluation method described in the embodiment described later, for example, a relative dielectric constant of less than 3.0 (preferably less than 2.8, less than 2.6, less than 2.5, etc.) can be obtained. And, according to one mode of the resin composition involved in the present embodiment, a cured product with excellent dielectric loss tangent (low dielectric loss tangent) can be obtained. According to one aspect of the resin composition involved in the present embodiment, in the evaluation method described in the examples described below, for example, a dielectric loss tangent of 0.0060 or less (preferably 0.0050 or less, 0.0045 or less, 0.0040 or less, 0.0035 or less, 0.0030 or less, etc.) can be obtained.
[0043] In the resin composition involved in the present embodiment, when the resin composition is heat treated at 120° C. for 30 minutes, a cured product with a tensile elastic modulus of 50 MPa or more is provided. From the viewpoint of easily suppressing the generation of wrinkles in the conductive component, the tensile elastic modulus of the cured product can be 80 MPa or more, 100 MPa or more, 150 MPa or more, 200 MPa or more, 250 MPa or more, 300 MPa or more, 350 MPa or more, 400 MPa or more, 410 MPa or more, 418 MPa or more, 440 MPa or more, 450 MPa or more, or 500 MPa or more. The tensile elastic modulus of the cured product can be 1000 MPa or less, 800 MPa or less, 600 MPa or less, 500 MPa or less, 400 MPa or less, or 300 MPa or less. From these viewpoints, the tensile modulus of the cured product can be 50 to 1000 MPa, 100 to 1000 MPa, 200 to 1000 MPa, 300 to 1000 MPa or 400 to 1000 MPa. The tensile modulus of the cured product can be adjusted by the type and content of the components such as the elastomer and the polymerizable compound. As the resin composition to be heat treated, a film-like resin composition with a thickness of 100 μm can be used.
[0044] The resin composition involved in the present embodiment contains an elastomer. As an elastomer, styrene-based elastomers, olefin-based elastomers, urethane-based elastomers, polyester-based elastomers, polyamide-based elastomers, silicone-based elastomers, etc. can be cited. From the viewpoint of easily suppressing the generation of the wrinkles in the conductive component and the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the elastomer can include a styrene-based elastomer.
[0045] The styrene-based elastomer may be a polymer having a styrene compound as a monomer unit (a polymer having a monomer unit derived from a styrene compound. Hereinafter, it is referred to as a "styrene-based polymer"). Examples of the styrene compound include styrene; alkyl styrenes such as methyl styrene, dimethyl styrene, trimethyl styrene, ethyl styrene, diethyl styrene, triethyl styrene, propyl styrene, butyl styrene, hexyl styrene, heptyl styrene, and octyl styrene; halogenated styrenes such as fluorostyrene, chlorostyrene, bromostyrene, dibromostyrene, and iodostyrene; nitrostyrene; acetylstyrene; methoxystyrene, and the like. From the viewpoint of easily suppressing the generation of wrinkles in the conductive member and from the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the styrene-based polymer may have styrene as a monomer unit.
[0046] Examples of the styrene-based polymer include styrene-butadiene random copolymers, styrene-butadiene-styrene block copolymers, styrene-butylene-butadiene-styrene block copolymers, styrene-isoprene-styrene block copolymers, styrene-ethylene-butylene-styrene block copolymers, styrene-ethylene-propylene-styrene block copolymers, and hydrogenated copolymers thereof.
[0047] From the viewpoint of easily suppressing the generation of wrinkles in the conductive part and the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the elastomer may include a styrene block copolymer. The styrene block copolymer may be a block copolymer having a monomer unit of a styrene compound and a monomer unit of another styrene compound, or a block copolymer having a monomer unit of a styrene compound and a monomer unit of a compound not corresponding to the styrene compound. From the viewpoint of easily suppressing the generation of wrinkles in the conductive part and the viewpoint of easily improving the tensile elastic modulus of the cured product, the elastomer may include a styrene-butadiene-styrene block copolymer.
[0048] The styrene polymer may be modified by carboxylic anhydride or may not be modified by carboxylic anhydride. As carboxylic anhydride, dicarboxylic anhydrides such as maleic anhydride, phthalic anhydride, and itaconic anhydride may be cited. From the viewpoint of easily obtaining a cured product with high adhesion to a conductive component, the elastomer may include a styrene block copolymer modified by carboxylic anhydride, a styrene block copolymer modified by maleic anhydride, a styrene-butadiene-styrene block copolymer modified by carboxylic anhydride, and a styrene-butadiene-styrene block copolymer modified by maleic anhydride.
[0049] From the viewpoint of easily suppressing the generation of wrinkles in the conductive component and the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, based on the total mass of styrene polymers or the total mass of styrene block copolymers, the content of the monomer unit of styrene compounds or the content of the monomer unit of styrene can be within the following range. The content of the monomer unit can be 5% by mass or more, 10% by mass or more, 15% by mass or more, 20% by mass or more, 25% by mass or more, 30% by mass or more, 35% by mass or more or 40% by mass or more. The content of the monomer unit can be 80% by mass or less, 75% by mass or less, 70% by mass or less, 65% by mass or less, 60% by mass or less, 55% by mass or less, 50% by mass or less, 45% by mass or less or 40% by mass or less. From these viewpoints, the content of the monomer unit may be 5-80 mass %, 5-60 mass %, 5-50 mass %, 20-80 mass %, 20-60 mass %, 20-50 mass %, 30-80 mass %, 30-60 mass % or 30-50 mass %.
[0050] From the viewpoint of easily suppressing the generation of wrinkles in the conductive component and easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the content of the styrene polymer or the content of the styrene block copolymer can be 50% by mass or more, more than 50% by mass, 70% by mass or more, 90% by mass or more, 95% by mass or more, or 99% by mass or more, based on the total mass of the elastomer. The elastomer contained in the resin composition can be substantially formed by a styrene polymer or a styrene block copolymer (based on the total mass of the elastomer contained in the resin composition, the content of the styrene polymer or the content of the styrene block copolymer is substantially 100% by mass).
[0051] The MFR (melt flow rate. 200°C, 5 kgf (49N). Unit: g / 10 min) of a styrene polymer or styrene block copolymer measured according to ISO 1133 may be within the following range. From the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the MFR may be 1 or more, 2 or more, 3 or more, 4 or more, 5 or more, or 6 or more. The MFR may be 7 or more. The MFR may be 10 or less, 9 or less, 8 or less, 7 or less, 6 or less, or 5 or less. From these viewpoints, the MFR may be 1 to 10, 3 to 8, 5 to 7, 4 to 6, or 6 to 8.
[0052] The Vicat softening temperature (test load 10N, heating rate 50°C / h) of the styrene polymer or styrene block copolymer measured according to ISO 306 may be within the following ranges. The Vicat softening temperature may be 50°C or higher, 60°C or higher, 70°C or higher, 72°C or higher, 75°C or higher, 80°C or higher, 81°C or higher, or 83°C or higher. From the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the Vicat softening temperature may be 100°C or lower, 90°C or lower, 85°C or lower, 83°C or lower, 81°C or lower, 80°C or lower, 75°C or lower, or 72°C or lower. From these viewpoints, the Vicat softening temperature may be 50-100°C, 60-90°C, or 70-85°C.
[0053] As the content of the elastomer, the content of the styrene polymer or the content of the styrene block copolymer, from the viewpoint of easily suppressing the generation of wrinkles in the conductive component and from the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the content A can be within the following range based on the total mass of the resin composition (excluding the mass of the organic solvent), the total amount of the elastomer, the polymerizable compound and the polymerization initiator, the total amount of the elastomer, the (meth)acrylic compound and the polymerization initiator, the total amount of the styrene block copolymer, the (meth)acrylic compound and the polymerization initiator, the total amount of the elastomer and the polymerizable compound, the total amount of the elastomer and the (meth)acrylic compound, or the total amount of the styrene block copolymer and the (meth)acrylic compound. The content A may be 20% by mass or more, more than 20% by mass, 21% by mass or more, 23% by mass or more, 25% by mass or more, 30% by mass or more, more than 30% by mass, 40% by mass or more, more than 40% by mass, 50% by mass or more, more than 50% by mass, 60% by mass or more, 65% by mass or more, 70% by mass or more, 75% by mass or more, 78% by mass or more, or 80% by mass or more. The content A may be 99% by mass or less, 95% by mass or less, 90% by mass or less, 85% by mass or less, 82% by mass or less, or 80% by mass or less. From these viewpoints, the content A may be 20 to 99% by mass, 20 to 90% by mass, 20 to 85% by mass, 50 to 99% by mass, 50 to 90% by mass, 50 to 85% by mass, 70 to 99% by mass, 70 to 90% by mass, or 70 to 85% by mass.
[0054] The resin composition involved in the present embodiment contains a polymerizable compound. As a polymerizable compound, a free radical polymerizable compound, a cationic polymerizable compound, an anionic polymerizable compound, etc. can be cited. From the viewpoint of easily suppressing the generation of wrinkles in the conductive component and the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the polymerizable compound can include a free radical polymerizable compound.
[0055] As polymerizable compounds, (meth) acrylic acid compounds (compounds with (meth) acryloyl groups), epoxy compounds (compounds with epoxy groups), maleimide compounds, vinylidene chloride halides, vinyl ether compounds, vinyl ester compounds, vinylamide compounds, aromatic vinyl compounds (such as vinyl pyridine compounds), allyl compounds, styrene compounds, (meth) acrylamide compounds, nadic imide compounds, natural rubber, isoprene rubber, butyl rubber, nitrile rubber, butadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene rubber, carboxylated nitrile rubber, oxetane compounds, lactone compounds, etc. From the viewpoint of easily suppressing the generation of wrinkles in conductive parts, the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in cured products, and the viewpoint of easily obtaining excellent transparency in cured products, polymerizable compounds may include compounds with ethylene unsaturated bonds, and may also include (meth) acrylic acid compounds. As (meth) acrylic acid compounds, compounds without epoxy groups may be used.
[0056] The (meth)acrylic compound may include at least one selected from the group consisting of a monofunctional (meth)acrylic compound and a polyfunctional (meth)acrylic compound (a bifunctional (meth)acrylic compound or a trifunctional or higher (meth)acrylic compound). For example, a "bifunctional (meth)acrylic compound" refers to a compound having a total of two acryloyl groups and two methacryloyl groups in one molecule. From the viewpoint of easily suppressing the generation of wrinkles in the conductive component and easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the (meth)acrylic compound may include a bifunctional (meth)acrylic compound.
[0057] Examples of the monofunctional (meth)acrylic acid compound include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, butoxyethyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octylheptyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, and (meth)acrylate. aliphatic (meth)acrylates such as stearyl (meth)acrylate, behenyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, ethoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, ethoxypolypropylene glycol (meth)acrylate, and mono(2-(meth)acryloyloxyethyl)succinate; cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate, dicyclopentyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and (meth)acrylate. alicyclic (meth)acrylates such as isobornyl (meth)acrylate, mono(2-(meth)acryloyloxyethyl)tetrahydrophthalic acid, mono(2-(meth)acryloyloxyethyl)hexahydrophthalic acid; benzyl (meth)acrylate, phenyl (meth)acrylate, o-biphenyl (meth)acrylate, 1-naphthyl (meth)acrylate, 2-naphthyl (meth)acrylate, phenoxyethyl (meth)acrylate, p-isopropylphenylphenoxyethyl (meth)acrylate, o-phenylphenoxyethyl (meth)acrylate, 1-naphthyloxyethyl (meth)acrylate, 2-naphthyloxyethyl (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, nonylphenoxypolyethylene glycol (meth)acrylate Aromatic (meth)acrylates such as esters, (meth)acrylate phenoxypolypropylene glycol ester, (meth)acrylate 2-hydroxy-3-phenoxypropyl ester, (meth)acrylate 2-hydroxy-3-(o-phenylphenoxy)propyl ester, (meth)acrylate 2-hydroxy-3-(1-naphthyloxy)propyl ester, (meth)acrylate 2-hydroxy-3-(2-naphthyloxy)propyl ester; heterocyclic (meth)acrylates such as (meth)acrylate 2-tetrahydrofurfuryl ester, N-(meth)acryloyloxyethyl hexahydrophthalimide, 2-(meth)acryloyloxyethyl-N-carbazole; (meth)acryloyl group-containing phosphates (e.g., (meth)acryloyloxyethyl acid phosphate); these caprolactone modified products, etc.
[0058] Examples of the bifunctional (meth)acrylic compound include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetrapropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, ethoxylated polypropylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, 1 aliphatic (meth)acrylates (e.g., alkanediol di(meth)acrylates) such as 6-hexanediol di(meth)acrylate, 2-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, nonanediol di(meth)acrylate (e.g., 1,9-nonanediol di(meth)acrylate), decanediol di(meth)acrylate (e.g., 1,10-decanediol di(meth)acrylate), dodecanediol di(meth)acrylate (e.g., 1,12-dodecanediol di(meth)acrylate), glycerol di(meth)acrylate, ethoxylated 2-methyl-1,3-propanediol di(meth)acrylate, and the like; cyclohexanedimethanol di(meth)acrylate, ethoxylated cyclohexanedimethanol di(meth)acrylate, and the like; acrylate, propoxylated cyclohexanedimethanol di(meth)acrylate, ethoxylated propoxylated cyclohexanedimethanol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, ethoxylated tricyclodecane dimethanol di(meth)acrylate, propoxylated tricyclodecane dimethanol di(meth)acrylate, ethoxylated propoxylated tricyclodecane dimethanol di(meth)acrylate, ethoxylated propoxylated tricyclodecane dimethanol di(meth)acrylate, ethoxylated hydrogenated bisphenol A di(meth)acrylate, propoxylated hydrogenated bisphenol A di(meth)acrylate, ethoxylated propoxylated hydrogenated bisphenol A di(meth)acrylate, ethoxylated hydrogenated bisphenol F di(meth)acrylate, propoxylated hydrogenated bisphenol F di(meth)acrylate, ethoxylated propoxylated hydrogenated bisphenol F di(meth)acrylate Alicyclic (meth)acrylates such as acrylates; aromatic (meth)acrylates such as ethoxylated bisphenol A di(meth)acrylate, propoxylated bisphenol A di(meth)acrylate, ethoxylated propoxylated bisphenol A di(meth)acrylate, ethoxylated bisphenol F di(meth)acrylate, propoxylated bisphenol F di(meth)acrylate, ethoxylated propoxylated bisphenol F di(meth)acrylate, ethoxylated bisphenol AF di(meth)acrylate, propoxylated bisphenol AF di(meth)acrylate, ethoxylated propoxylated bisphenol AF di(meth)acrylate, ethoxylated fluorene di(meth)acrylate, propoxylated fluorene di(meth)acrylate, and ethoxylated propoxylated fluorene di(meth)acrylate;Heterocyclic (meth)acrylates such as dioxypropylene glycol di(meth)acrylate, ethoxylated isocyanuric acid di(meth)acrylate, propoxylated isocyanuric acid di(meth)acrylate, and ethoxylated propoxylated isocyanuric acid di(meth)acrylate; these caprolactone modified products; aliphatic epoxy (meth)acrylates such as neopentyl glycol epoxy (meth)acrylate; alicyclic epoxy (meth)acrylates such as cyclohexanedimethanol epoxy (meth)acrylate, hydrogenated bisphenol A epoxy (meth)acrylate, and hydrogenated bisphenol F epoxy (meth)acrylate; aromatic epoxy (meth)acrylates such as resorcinol epoxy (meth)acrylate, bisphenol A epoxy (meth)acrylate, bisphenol F epoxy (meth)acrylate, bisphenol AF epoxy (meth)acrylate, and fluorene epoxy (meth)acrylate, etc.;
[0059] Examples of the trifunctional or higher-functional (meth)acrylic compound include trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, ethoxylated propoxylated trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, ethoxylated pentaerythritol tri(meth)acrylate, propoxylated pentaerythritol tri(meth)acrylate, ethoxylated propoxylated pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, propoxylated pentaerythritol tetra(meth)acrylate, ethoxylated propoxylated pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and ethoxylated propoxylated pentaerythritol tri(meth)acrylate. Aliphatic (meth)acrylates such as oxylated pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ethoxylated dipentaerythritol hexa(meth)acrylate, and propoxylated dipentaerythritol hexa(meth)acrylate; heterocyclic (meth)acrylates such as ethoxylated isocyanurate tri(meth)acrylate, propoxylated isocyanurate tri(meth)acrylate, and ethoxylated propoxylated isocyanurate tri(meth)acrylate; these caprolactone modified products; aromatic epoxy (meth)acrylates such as phenol novolac type epoxy (meth)acrylate and cresol novolac type epoxy (meth)acrylate, etc.
[0060] From the viewpoint of easily suppressing the generation of wrinkles in the conductive component and easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the (meth) acrylic compound may include aliphatic (meth) acrylate. From the viewpoint of easily suppressing the generation of wrinkles in the conductive component and easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the (meth) acrylic compound may include alkanediol di(meth) acrylate, or may include at least one selected from the group consisting of nonanediol di(meth) acrylate and dodecanediol di(meth) acrylate. The (meth) acrylic compound may include an acrylic compound. From the viewpoint of easily obtaining a low dielectric loss tangent in the cured product, the (meth) acrylic compound may include a methacrylic compound.
[0061] From the viewpoint of facilitating adjustment of dielectric properties (relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the (meth)acrylic compound may contain a compound represented by the following general formula (I).
[0062]
[0063] In the formula, R 1 represents a group containing 9 or less carbon atoms and 2 or more oxygen atoms, R 2a and R 2b Each independently represents a hydrogen atom or a methyl group.
[0064] R 1 The number of carbon atoms in the R is 1 to 9. From the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, R 1 The number of carbon atoms in R may be 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, or 8 or more. From the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, R 1 The number of oxygen atoms in R may be 6 or less, 5 or less, 4 or less, 3 or less, or 2 or less. 1 It can be a hydrocarbon group with oxygen atoms bonded at both ends, or it can be a "-OC n H 2n -O-" group (n = 1 to 9). From the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the (meth)acrylic compound may contain R 1 Compounds without a ring structure may also include R 1 Compounds that do not have an alicyclic ring.
[0065] From the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the content of the compound represented by the general formula (I) may be 50% by mass or more, more than 50% by mass, 70% by mass or more, 90% by mass or more, 95% by mass or more, 99% by mass or more, or more than 99% by mass, based on the total mass of the polymerizable compound or the total mass of the (meth)acrylic compound. The polymerizable compound or (meth)acrylic compound contained in the resin composition is substantially composed of the compound represented by the general formula (I) (based on the total mass of the polymerizable compound or (meth)acrylic compound contained in the resin composition, the content of the compound represented by the general formula (I) is substantially 100% by mass).
[0066] The (meth)acrylic compound may contain a (meth)acrylic compound having a hydroxyl group, or may not contain a (meth)acrylic compound having a hydroxyl group. The content of the (meth)acrylic compound having a hydroxyl group may be 5% by mass or less, less than 5% by mass, 1% by mass or less, 0.1% by mass or less, 0.01% by mass or less, or substantially 0% by mass, based on the total mass of the polymerizable compound or the total mass of the (meth)acrylic compound.
[0067] From the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the molecular weight of the (meth)acrylic compound may be in the following range. The molecular weight of the (meth)acrylic compound may be 80 or more, 100 or more, 120 or more, 150 or more, 180 or more, 200 or more, 220 or more, 250 or more, 260 or more, 280 or more, 290 or more, 300 or more, or 320 or more. The molecular weight of the (meth)acrylic compound may be 1000 or less, 800 or less, 600 or less, 550 or less, 500 or less, 450 or less, 400 or less, 350 or less, 320 or less, 300 or less, or 280 or less. From these viewpoints, the molecular weight of the (meth)acrylic compound may be 80-1000, 80-500, 80-400, 80-300, 200-1000, 200-500, 200-400, 200-300, 250-1000, 250-500, 250-400, 250-300, 300-1000, 300-500 or 300-400.
[0068] As the content of the polymerizable compound or the content of the (meth) acrylic compound, from the viewpoint of easily suppressing the generation of wrinkles in the conductive component and easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the content B1 can be within the following ranges relative to 100 parts by mass of the elastomer, 100 parts by mass of the styrene polymer or 100 parts by mass of the styrene block copolymer. The content B1 can be 1 part by mass or more, 5 parts by mass or more, 10 parts by mass or more, 15 parts by mass or more, 20 parts by mass or more, or 25 parts by mass or more. The content B1 can be 300 parts by mass or less, 200 parts by mass or less, 100 parts by mass or less, 80 parts by mass or less, 60 parts by mass or less, 50 parts by mass or less, 40 parts by mass or less, 30 parts by mass or less, or 25 parts by mass or less. From these viewpoints, the content B1 may be 1 to 300 parts by mass, 10 to 300 parts by mass, 20 to 300 parts by mass, 1 to 100 parts by mass, 10 to 100 parts by mass, 20 to 100 parts by mass, 1 to 50 parts by mass, 10 to 50 parts by mass or 20 to 50 parts by mass.
[0069] As the content of the polymerizable compound or the content of the (meth) acrylic compound, from the viewpoint of easily suppressing the generation of wrinkles in the conductive member and easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the content B2 may be within the following range based on the total mass of the resin composition (excluding the mass of the organic solvent), the total amount of the elastomer, the polymerizable compound and the polymerization initiator, the total amount of the elastomer, the (meth) acrylic compound and the polymerization initiator, the total amount of the styrene block copolymer, the (meth) acrylic compound and the polymerization initiator, the total amount of the elastomer and the polymerizable compound, the total amount of the elastomer and the (meth) acrylic compound, or the total amount of the styrene block copolymer and the (meth) acrylic compound. The content B2 may be 1% by mass or more, 5% by mass or more, 10% by mass or more, 15% by mass or more, 18% by mass or more, or 20% by mass or more. The content B2 may be 80% by mass or less, less than 80% by mass, 70% by mass or less, less than 70% by mass, 60% by mass or less, less than 60% by mass, 50% by mass or less, less than 50% by mass, 40% by mass or less, 35% by mass or less, 30% by mass or less, 25% by mass or less, or 20% by mass or less. From these viewpoints, the content B2 may be 1 to 80% by mass, 1 to 50% by mass, 1 to 30% by mass, 10 to 80% by mass, 10 to 50% by mass, 10 to 30% by mass, 15 to 80% by mass, 15 to 50% by mass, or 15 to 30% by mass.
[0070] The resin composition according to the present embodiment contains a polymerization initiator. As the polymerization initiator, a thermal polymerization initiator can be used.
[0071] Examples of the thermal polymerization initiator include ketone peroxides such as methyl ethyl ketone peroxide, cyclohexanone peroxide, and methylcyclohexanone peroxide; peroxyketals such as 1,1-bis(tert-butylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)-2-methylcyclohexane, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-hexylperoxy)cyclohexane, and 1,1-bis(tert-hexylperoxy)-3,3,5-trimethylcyclohexane; hydroperoxides such as p-menthane hydroperoxide; α,α'-bis(tert-butylperoxy)diisopropylbenzene, diisopropylbenzene peroxide, tert-butylisopropylbenzene peroxide, di-tert-butylisopropylbenzene peroxide, and di-tert-butylisopropylbenzene peroxide. peroxides, such as dialkyl peroxides; diacyl peroxides such as octanoyl peroxide, lauroyl peroxide, stearyl peroxide, and benzoyl peroxide; peroxy carbonates such as bis(4-tert-butylcyclohexyl)peroxydicarbonate, di-2-ethoxyethyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, and di-3-methoxybutyl peroxycarbonate; tert-butyl peroxypivalate, tert-hexyl peroxypivalate, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, 2,5-dimethyl-2,5-bis(2-ethylhexanoyl peroxy)hexane, tert-hexyl peroxy-2-ethylhexanoate, tert-butyl peroxy- 2-ethylhexanoate, tert-butyl peroxyisobutyrate, tert-hexyl peroxyisopropyl monocarbonate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxylaurate, tert-butyl peroxyisopropyl monocarbonate, tert-butyl peroxy-2-ethylhexyl monocarbonate, tert-butyl peroxybenzoate, tert-hexyl peroxybenzoate, 2,5-dimethyl-2,5-bis(benzoylperoxy)hexane, tert-butyl peroxyacetate and other peroxyesters; phthalic anhydride, maleic anhydride, trimellitic anhydride, hexahydrophthalic anhydride, tetrahydrophthalic anhydride, methyl nadic anhydride, nadic anhydride, glutaric anhydride, dimethyl glutaric anhydride, diethyl glutaric anhydride, Acid anhydrides such as succinic anhydride, methylhexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, 1,2,3,4-cyclobutanetetracarboxylic anhydride, 4,4'-diphthalic anhydride, 4,4'-carbonyldiphthalic anhydride, 4,4'-sulfonyldiphthalic anhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 4,4'-oxydiphthalic anhydride, 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, and 2,3,6,7-naphthalenetetracarboxylic anhydride; azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), and 2,2'-azobis(4-methoxy-2'-dimethylvaleronitrile); etc.
[0072] From the viewpoint of easily suppressing the generation of wrinkles in the conductive member and easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the polymerization initiator may include a thermal free radical polymerization initiator or a thermal cationic polymerization initiator. From the viewpoint of easily suppressing the generation of wrinkles in the conductive member and easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the polymerization initiator may include a peroxide, a peroxyester, or 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane.
[0073] The content of the polymerization initiator may be within the following ranges based on the total mass of the resin composition (excluding the mass of the organic solvent), the total amount of the elastomer, the polymerizable compound and the polymerization initiator, the total amount of the elastomer, the (meth) acrylic compound and the polymerization initiator, the total amount of the styrene block copolymer, the (meth) acrylic compound and the polymerization initiator, the total amount of the elastomer and the polymerizable compound, the total amount of the elastomer and the (meth) acrylic compound or the total amount of the styrene block copolymer and the (meth) acrylic compound. From the viewpoint of easily suppressing the generation of wrinkles in the conductive member, the viewpoint of easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, and the viewpoint of easily obtaining excellent curability, the content of the polymerization initiator may be 0.01% by mass or more, 0.05% by mass or more, 0.1% by mass or more, more than 0.1% by mass, 0.3% by mass or more, 0.5% by mass or more, 0.8% by mass or more, 0.9% by mass or more, or 1% by mass or more. From the viewpoint of easily suppressing the generation of wrinkles in the conductive component and easily obtaining excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.) in the cured product, the content of the polymerization initiator can be 10% by mass or less, 8% by mass or less, 5% by mass or less, 3% by mass or less, 2% by mass or less, less than 2% by mass, 1.5% by mass or less, or 1% by mass or less. From these viewpoints, the content of the polymerization initiator can be 0.01 to 10% by mass, 0.01 to 5% by mass, 0.01 to 2% by mass, 0.1 to 10% by mass, 0.1 to 5% by mass, 0.1 to 2% by mass, 0.5 to 10% by mass, 0.5 to 5% by mass, or 0.5 to 2% by mass.
[0074] The resin composition involved in the present embodiment may contain additives other than elastomer, polymerizable compound and thermal polymerization initiator. As such additives, curing accelerators, antioxidants, ultraviolet absorbers, visible light absorbers, colorants, plasticizers, stabilizers, fillers (fillers), reducing agents, bicarbonates, etc. can be cited. As reducing agents, vanadium acetylacetonate, vanadium acetylacetonate, cobalt acetylacetonate, copper acetylacetonate, vanadium oxynaphthenate, vanadium oxystearate, copper naphthenate, copper acetate, cobalt octoate, etc. can be cited.
[0075] The content of the filler may be 100% by mass or less, less than 100% by mass, 50% by mass or less, 20% by mass or less, less than 20% by mass, 10% by mass or less, 1% by mass or less, 0.1% by mass or less, or substantially 0% by mass, based on the total amount of the elastomer and the polymerizable compound, the total amount of the elastomer and the (meth)acrylic compound, or the total amount of the styrene block copolymer and the (meth)acrylic compound. The content of the reducing agent may be 0.01% by mass or less, less than 0.01% by mass, 0.001% by mass or less, or substantially 0% by mass, relative to 100 parts by mass of the polymerizable compound or 100 parts by mass of the (meth)acrylic compound. The content of the bicarbonate may be 0.1% by mass or less, less than 0.1% by mass, 0.01% by mass or less, 0.001% by mass or substantially 0% by mass, relative to 100 parts by mass of the polymerizable compound or 100 parts by mass of the (meth)acrylic compound.
[0076] The resin composition involved in this embodiment may contain an organic solvent. The resin composition involved in this embodiment can be used as a resin varnish by diluting with an organic solvent. As an organic solvent, aromatic hydrocarbons such as toluene, xylene, mesitylene, isopropylbenzene, and p-isopropylbenzene can be cited; cyclic ethers such as tetrahydrofuran and 1,4-dioxane; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, and 4-hydroxy-4-methyl-2-pentanone; esters such as methyl acetate, ethyl acetate, butyl acetate, methyl lactate, ethyl lactate, and γ-butyrolactone; carbonates such as ethylene carbonate and propylene carbonate; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.
[0077] The total light transmittance per 100 μm thickness of the layer containing the resin composition involved in the present embodiment or the cured product involved in the present embodiment can be 90% or more or 91% or more. The total light transmittance can be measured according to the method specified in JIS K 7136, for example, using NDH-5000 (product name) manufactured by NIPPON DENSHOKU INDUSTRIES Co., Ltd. The total light transmittance described below can also be measured using the same method.
[0078] The laminated body according to the present embodiment includes a base film (support film) and a transparent resin layer disposed on the base film, and the transparent resin layer includes at least one selected from the group consisting of the resin composition according to the present embodiment and a cured product thereof.
[0079] As the constituent material of the substrate film, polyester (polyethylene terephthalate (PET), polybutylene terephthalate, polyethylene naphthalate, etc.), polyolefin (polyethylene, polypropylene, cycloolefin polymer, etc.), polycarbonate, polyamide, polyimide, polyamideimide, polyetherimide, polyether sulfide, polyether sulfone, polyether ketone, polyphenylene ether, polyphenylene sulfide, etc. can be mentioned. The thickness of the substrate film can be 1 to 200 μm, 10 to 100 μm, 20 to 80 μm or 20 to 50 μm.
[0080] From the viewpoint of easily obtaining excellent transmittance and easily thinning the transparent antenna, the thickness of the transparent resin layer can be 1000 μm or less, 800 μm or less, 500 μm or less, 300 μm or less, 250 μm or less, 200 μm or less, 150 μm or less, 100 μm or less, 80 μm or less, 50 μm or less, 30 μm or less, 25 μm or less, 20 μm or less, 15 μm or less, 12 μm or less, 10 μm or less, 9 μm or less or 8 μm or less. From the perspective of reducing transmission loss and facilitating improving antenna characteristics, the thickness of the transparent resin layer can be greater than 0.1 μm, greater than 0.5 μm, greater than 0.75 μm, greater than 1 μm, greater than 2 μm, greater than 3 μm, greater than 5 μm, greater than 6 μm, greater than 7 μm, greater than 8 μm, greater than 10 μm, greater than 20 μm, greater than 30 μm, greater than 40 μm, greater than 50 μm, greater than 80 μm or greater than 100 μm. From these viewpoints, the thickness of the transparent resin layer can be 0.1 to 1000 μm, 1 to 1000 μm, 10 to 500 μm, 20 to 200 μm, 50 to 200 μm, 0.1 to 500 μm, 0.1 to 100 μm, 0.5 to 250 μm, 0.5 to 150 μm, 0.75 to 100 μm, 1 to 50 μm, 2 to 30 μm, 3 to 20 μm or 5 to 20 μm.
[0081] A first aspect of the laminated body according to the present embodiment may include a protective film disposed on the transparent resin layer. A second aspect of the laminated body according to the present embodiment may include a conductive member disposed on the transparent resin layer.
[0082] As the constituent material of the protective film, the constituent materials mentioned above as the constituent material of the base film can be used. The protective film can be the same film as the base film or a film different from the base film. The thickness of the protective film can be 1 to 200 μm, 10 to 100 μm, 20 to 80 μm or 20 to 50 μm.
[0083] The conductive component may be solid or may have a patterned portion (may be patterned). In a conductive component having a patterned portion (hereinafter referred to as a "patterned conductive component"), a portion or all of the conductive component may be patterned (the same also applies to the following description related to the case where the conductive component has a patterned portion). Examples of the shape of the patterned portion include a mesh shape, a spiral shape, and the like. In the case of using a transparent antenna having a solid conductive component, the conductive component may be patterned (e.g., mesh processing). The patterned (e.g., mesh) conductive component may be composed of wires (e.g., metal wires). Examples of the constituent materials of the conductive component include metal materials, carbon materials (e.g., graphene), conductive polymers, and the like. Examples of metal materials include copper, silver, gold, and the like. From the viewpoint of easily obtaining excellent conductivity and easily reducing manufacturing costs, the conductive component may contain copper.
[0084] The conductive component can be a single layer or a multilayer. The multilayer conductive component can, for example, have a first conductive component (e.g., a metal component) disposed on a transparent resin layer, and a second conductive component (e.g., a metal component) disposed on the first conductive component. At least one selected from the group consisting of the first conductive component and the second conductive component can be solid, or it can have a patterned (e.g., mesh) portion. The second conductive component can be used as a protective layer to suppress contamination, damage, etc. of the first conductive component, thereby also being able to improve the operability of the laminate. At least one selected from the group consisting of the first conductive component and the second conductive component can contain copper.
[0085] The thickness of the conductive component (the total thickness in the case where the conductive component is multi-layered), the thickness of the first conductive component or the thickness of the second conductive component can be within the following range. From the perspective that the conductive component is not easily damaged and that a solid conductive component is easily patterned (e.g., mesh processing), the thickness can be 50 μm or less, 45 μm or less, 40 μm or less, 35 μm or less, 30 μm or less, 25 μm or less, 20 μm or less, 18 μm or less, 15 μm or less, 10 μm or less, 8 μm or less, 5 μm or less, 3 μm or less or 2 μm or less. From the perspective of easily obtaining excellent elongation, the thickness can be 0.1 μm or more, 0.3 μm or more, 0.5 μm or more, 0.8 μm or more, 1 μm or more, 1.2 μm or more, 1.5 μm or more or 2 μm or more. From these viewpoints, the thickness may be 0.1 to 50 μm, 0.1 to 30 μm, 0.1 to 20 μm, 0.1 to 10 μm, 0.5 to 5 μm or 1 to 3 μm.
[0086] The thickness of the first conductive component may be smaller than the thickness of the second conductive component. In the case where the conductive component is multi-layered, the thickness (total thickness) of the conductive component or the thickness of the second conductive component may be greater than 3 μm, greater than 5 μm, greater than 8 μm, greater than 10 μm, greater than 15 μm, greater than 18 μm or greater than 20 μm.
[0087] The laminated body involved in the second embodiment may include a protective film disposed on the conductive component. As the protective film, the protective film described above can be used as the protective film in the laminated body involved in the first embodiment. A demoulding treatment may be applied to at least a portion of one side of the conductive component side in the protective film, or a peeling layer may be configured on at least a portion of one side of the conductive component side in the protective film. For example, the laminated body involved in the second embodiment may include a substrate film, a transparent resin layer, a conductive component and a protective film, the conductive component is a single layer, and a demoulding treatment is applied to at least a portion of one side of the conductive component side in the protective film.
[0088] In the laminated body involved in the second embodiment, as a layer comprising at least one selected from the group consisting of a photosensitive composition and a cured product thereof, a layer L disposed on a conductive component may be provided. The photosensitive composition has photosensitivity to active light (ultraviolet rays, etc.), and may have positive photosensitivity or negative photosensitivity. The photosensitive composition may have photocurability that is cured by light irradiation. Layer L may be either before or after light irradiation, or may have at least one selected from the group consisting of an uncured portion and a cured portion. Layer L may be either before or after light irradiation, or may have at least one selected from the group consisting of an unexposed portion and an exposed portion. The constituent material of the photosensitive composition is not particularly limited.
[0089] Figure 1 and Figure 2 It is a schematic cross-sectional view showing an example of a laminated body. Figure 1 The laminate 10 of (a) includes a base film 10a, a transparent resin layer 10b disposed on the base film 10a, and a protective film 10c disposed on the transparent resin layer 10b. The transparent resin layer 10b is formed of the resin composition according to the present embodiment or the cured product according to the present embodiment. Figure 1 The laminate 20 of (b) includes a base film 20a, a transparent resin layer 20b disposed on the base film 20a, and a conductive member 20c disposed on the transparent resin layer 20b. The transparent resin layer 20b is formed of the resin composition according to the present embodiment or the cured product according to the present embodiment. Figure 2 The laminate 30 includes a substrate film 30a, a transparent resin layer 30b disposed on the substrate film 30a, a conductive member 30c disposed on the transparent resin layer 30b, and a conductive member 30d disposed on the conductive member 30c. The transparent resin layer 30b is formed of the resin composition involved in this embodiment or the cured product involved in this embodiment.
[0090] The resin composition and cured product thereof according to the present embodiment can be used in a transparent antenna and a method for manufacturing the same. In a transparent antenna, the applicable part of the resin composition and cured product thereof according to the present embodiment is not particularly limited. Regarding the case of using the resin composition according to the present embodiment, hereinafter, the substrate obtained by curing the resin composition of the transparent resin layer in the curing process is referred to as a "transparent substrate", and the layer that can contain the state before curing the resin composition of the transparent resin layer in the curing process is referred to as a "transparent resin layer".
[0091] The first mode of the transparent antenna involved in the present embodiment comprises a transparent substrate and a conductive component arranged on the transparent substrate, and the transparent substrate comprises a cured product of the resin composition involved in the present embodiment. The transparent antenna involved in the first mode may comprise a covering component arranged on the conductive component, and the covering component may comprise a cured product of the resin composition involved in the present embodiment, or may not comprise a cured product of the resin composition involved in the present embodiment (or may comprise a cured product of a resin composition that does not correspond to the resin composition involved in the present embodiment). The second mode of the transparent antenna involved in the present embodiment comprises a conductive component and a covering component arranged on the conductive component, and the covering component comprises a cured product of the resin composition involved in the present embodiment. The second mode of the transparent antenna involved in the present embodiment may comprise a transparent substrate, and the conductive component may be arranged on the transparent substrate. In the transparent antenna involved in the second mode, the transparent substrate may comprise a cured product of the resin composition involved in the present embodiment, or may not comprise a cured product of the resin composition involved in the present embodiment (or may comprise a cured product of a resin composition that does not correspond to the resin composition involved in the present embodiment). The transparent antenna according to the present embodiment may include a transparent substrate, a conductive member disposed on the transparent substrate, and a covering member disposed on the conductive member, wherein at least one selected from the group consisting of the transparent substrate and the covering member includes a cured product of the resin composition according to the present embodiment.
[0092] In the transparent antenna involved in this embodiment, the covering component can be arranged on at least a part (a part or all) of the conductive component. The covering component can be arranged on at least a part (a part or all) of the transparent substrate. In addition to the part arranged on the conductive component, the covering component can also have a part arranged on the transparent substrate but not arranged on the conductive component. The conductive component is arranged on a part of the transparent substrate (for example, a part of the main surface of the transparent substrate), so that the covering component (transparent component) can be arranged on the transparent substrate and the conductive component. The covering component can protect the conductive component by covering the conductive component. The covering component can protect the transparent substrate by covering the transparent substrate.
[0093] The covering member may abut against the conductive member. The covering member may abut against the transparent substrate or may not abut against the transparent substrate. The transparent substrate may abut against a transparent member different from the covering member (for example, a supporting member described later). The covering member may abut against a transparent member different from the transparent substrate (for example, a protective member described later).
[0094] In the transparent antenna involved in the present embodiment, at least one component selected from the group consisting of a transparent substrate and a covering component can contain a cured product of the resin composition involved in the present embodiment. In the case where one of the transparent substrate and the covering component (hereinafter referred to as "component A") does not contain a cured product of the resin composition involved in the present embodiment, component A can be formed of a material having a total light transmittance of 90% or more or 91% or more per 100 μm thickness. As the constituent material of component A, polyolefins (polyethylene, polypropylene, cycloolefin polymer (COP), etc.), polyesters (polyethylene terephthalate (PET), polybutylene terephthalate, polyethylene naphthalate, etc.), polycarbonate, polyamide, polyimide, polyamideimide, polyetherimide, polyether sulfide, polyether sulfone, polyether ketone, polyphenylene ether, polyphenylene sulfide, etc. can be cited. For example, component A can contain a cycloolefin polymer.
[0095] In the transparent antenna involved in this embodiment, as the structure of the conductive component, the above-mentioned structure can be used for the conductive component in the laminated body involved in the second embodiment. For example, the conductive component can contain copper. The conductive component can be solid or have a patterned (e.g., mesh) portion. The conductive component can be a single layer. As the thickness of the transparent substrate, the above-mentioned thickness can be used for the transparent resin layer of the laminated body involved in this embodiment.
[0096] The transparent antenna involved in this embodiment may include a supporting member supporting a transparent substrate, that is, it may include a supporting member, a transparent substrate arranged on the supporting member, and a conductive member arranged on the transparent substrate. The transparent antenna involved in this embodiment may include a protective member arranged on a covering member, that is, it may include a transparent substrate, a conductive member arranged on the transparent substrate, a covering member arranged on the conductive member, and a protective member arranged on the covering member.
[0097] The shapes of the supporting member and the protective member are not particularly limited, and may be film-shaped, substrate-shaped, indefinitely shaped, etc. As constituent materials of the supporting member and the protective member, resin materials, inorganic materials, etc. may be cited. As resin materials, polyolefins (polyethylene, polypropylene, cycloolefin polymers, etc.), polyesters (polyethylene terephthalate (PET), polybutylene terephthalate, polyethylene naphthalate, etc.), polycarbonates, polyamides, polyimides, polyamide-imides, polyetherimides, polyether sulfides, polyether sulfones, polyether ketones, polyphenylene ethers, polyphenylene sulfides, etc. may be cited. As inorganic materials, glass, etc. may be cited. The supporting member and the protective member are not limited to being transparent, and may be transparent members (transparent films, transparent substrates, etc.) or opaque members. The supporting member and the protective member may be formed of a material having a total light transmittance of more than 90% per a thickness of 100 μm. From the viewpoint of low dielectric, the supporting member may contain polyolefins.
[0098] In the first mode of the method for manufacturing the transparent antenna involved in the present embodiment, as a method for obtaining the transparent antenna involved in the first mode, a processing step of patterning (e.g., processing into a mesh) at least a portion of a conductive component (solid conductive component) disposed on a transparent resin layer comprising at least one selected from the group consisting of the resin composition involved in the present embodiment and its cured product. In the processing step, a patterned (e.g., mesh-like) conductive component can be obtained by etching the conductive component in a state where a patterned resist layer is disposed on the conductive component of a laminate having a transparent resin layer and a conductive component disposed on the transparent resin layer. The resist layer can be removed after etching the conductive component. The patterned resist layer can be obtained by removing the uncured portion or the cured portion of the photosensitive layer (a layer comprising a photosensitive composition) disposed on the conductive component. For example, the patterned resist layer can be obtained by irradiating (exposing) a photosensitive layer (a layer containing a photosensitive composition) disposed on a conductive member with active light (e.g., ultraviolet rays), and then removing (developing) the unexposed portion (when the photosensitive layer has negative photosensitivity) or the exposed portion (when the photosensitive layer has positive photosensitivity). As the photosensitive layer, the above-mentioned layer L can be used.
[0099] The laminated body having the conductive member disposed on the transparent resin layer can be obtained by forming the conductive member on the transparent resin layer comprising at least one selected from the group consisting of the resin composition involved in the present embodiment and the cured product thereof, for example, after removing the protective film of the laminated body involved in the first embodiment, the conductive member can be formed on the transparent resin layer. The laminated body having the conductive member disposed on the transparent resin layer can be the laminated body involved in the second embodiment.
[0100] The manufacturing method of the transparent antenna involved in the first embodiment may include a curing step of curing the transparent resin layer (resin composition of the transparent resin layer) to obtain a cured product (transparent substrate) before, after, or before or after the processing step. In the curing step, the uncured resin composition may be heated to cure the resin composition. The curing step in another embodiment of the manufacturing method of the transparent antenna described below may be the same as the curing step in the manufacturing method of the transparent antenna involved in the first embodiment.
[0101] In the second mode of the method for manufacturing the transparent antenna involved in the present embodiment, as a method for obtaining the transparent antenna involved in the first mode, a formation process of forming a patterned (e.g., mesh-shaped) conductive component is formed in a state where a patterned resist layer is arranged on a transparent resin layer comprising at least one selected from the group consisting of the resin composition involved in the present embodiment and its cured product. In the formation process, the resist layer can be used as a mask, and a patterned (e.g., mesh-shaped) conductive component can be formed by plating or sputtering. The resist layer can be removed after the formation process. The method for manufacturing the transparent antenna involved in the second mode may include a curing process of curing the transparent resin layer (resin composition of the transparent resin layer) before the formation process, after the formation process, or before and after the formation process to obtain a cured product (transparent substrate).
[0102] The third mode of the method for manufacturing the transparent antenna involved in the present embodiment includes a removal step of removing the substrate film in the laminate involved in the second mode. The conductive component in the laminate involved in the second mode may have a patterned (e.g., mesh-like) portion. In the case where the transparent resin layer of the laminate during the removal step contains a cured product (in the case where the transparent resin layer is a transparent substrate), a laminate of a transparent substrate and a conductive component (a patterned (e.g., mesh-like) conductive component, etc.) can be obtained as a transparent antenna through the removal step. The method for manufacturing the transparent antenna involved in the third mode may include a curing step of curing the transparent resin layer (the resin composition of the transparent resin layer) before the removal step, after the removal step, or before and after the removal step to obtain a cured product (transparent substrate).
[0103] The fourth mode of the method for manufacturing the transparent antenna involved in the present embodiment includes a lamination step of laminating the transparent resin layer in the laminated body involved in the present embodiment on a supporting member. As the supporting member, the above-mentioned supporting member can be used for the transparent antenna. In the lamination step, the transparent resin layer can be laminated on the supporting member in a state where the base film in the laminated body involved in the present embodiment is removed, or the transparent resin layer can be laminated on the supporting member in a state where the protective film in the laminated body involved in the first mode is removed. The method for manufacturing the transparent antenna involved in the fourth mode may include a removal step A of removing the base film in the laminated body involved in the present embodiment, and may also include a removal step B of removing the protective film in the laminated body involved in the first mode.
[0104] In the case of using the laminated body involved in the second embodiment, in the lamination process, the transparent resin layer and the conductive component can be laminated on the supporting component in a state where the transparent resin layer is located closer to the supporting component than the conductive component, or the transparent resin layer and the conductive component can be laminated on the supporting component in a state where the transparent resin layer is in contact with the supporting component. In the lamination process, the conductive component can be solid or have a patterned (e.g., mesh) portion. In the lamination process, the transparent resin layer and the conductive component can be laminated on the supporting component in a state where the base film in the laminated body involved in the second embodiment is removed. In the case where the laminated body involved in the second embodiment has a protective film disposed on the conductive component, in the lamination process, the transparent resin layer, the conductive component and the protective film can be laminated on the supporting component in a state where the transparent resin layer is located closer to the supporting component than the conductive component (the conductive component is located closer to the transparent resin layer than the protective film). When the laminated body according to the second embodiment includes a base film, a transparent resin layer, a conductive member, and a protective film, the method for manufacturing a transparent antenna according to the fourth embodiment may include a removal step B of removing the protective film after the removal step A and the lamination step. When the laminated body according to the second embodiment includes the above-mentioned layer L, in the lamination step, the transparent resin layer, the conductive member, and the layer L may be laminated on the support member in a state where the transparent resin layer is located closer to the support member than the conductive member.
[0105] In the case where the supporting member and the conductive member are stacked with good adhesion in a laminate having a supporting member and a conductive member arranged on the supporting member, surface treatment (plasma treatment, corona treatment, etc.) is sometimes applied to the supporting member, and the manufacturing process of the laminate may become complicated. For example, when polyolefin is used as the constituent material of the supporting member, since the adhesion between polyolefin and the conductive member (for example, metal materials such as copper) is low, surface treatment is sometimes required to obtain sufficient adhesion. On the other hand, according to the manufacturing method of the transparent antenna involved in the fourth embodiment, sufficient adhesion between the supporting member and the conductive member is obtained through the transparent substrate, and at the same time, a laminate of the supporting member and the conductive member (a laminate having a supporting member, a transparent substrate and a conductive member) can be obtained as a transparent antenna. For example, sufficient adhesion between the supporting member containing polyolefin and the conductive member containing copper can be obtained through the transparent substrate, and at the same time, a transparent antenna can be obtained. Furthermore, according to the manufacturing method of the transparent antenna involved in the fourth embodiment, by laminating the laminated body involved in the second embodiment on the supporting member, the transparent resin layer and the conductive member can be supplied to the supporting member together, and each component does not need to be formed on the supporting member each time the transparent antenna is manufactured, and the transparent antenna can be obtained by a simple method. In the case where the laminated body involved in the second embodiment has the above-mentioned layer L, according to the manufacturing method of the transparent antenna involved in the fourth embodiment, by laminating the laminated body involved in the second embodiment on the supporting member, the transparent resin layer, the conductive member and the layer L can be supplied to the supporting member together, and each component does not need to be formed on the supporting member each time the transparent antenna is manufactured, and the transparent antenna can be obtained by a simple method. In addition, according to the manufacturing method of the transparent antenna involved in the fourth embodiment, as the constituent material of the transparent resin layer or the transparent substrate, by using a material having excellent dielectric properties (low relative dielectric constant, dielectric loss tangent, etc.), a transparent antenna having excellent antenna characteristics can be obtained.
[0106] In the method for manufacturing a transparent antenna according to the fourth aspect, the transparent resin layer in the removal step A, the removal step B, and the lamination step may be uncured or may be a cured product. The method for manufacturing a transparent antenna according to the fourth aspect may include a curing step of curing the transparent resin layer (resin composition of the transparent resin layer) to obtain a cured product (transparent substrate) before the removal step A, before the removal step B, before the lamination step, after the removal step A, after the removal step B, after the lamination step, before and after the removal step A, before and after the removal step B, or before and after the lamination step.
[0107] In the method for manufacturing a transparent antenna according to the fourth embodiment, the conductive component in the removal step A, the removal step B, and the stacking step may be solid or may have a patterned (e.g., mesh-like) portion. When the conductive component is solid, the method for manufacturing a transparent antenna according to the fourth embodiment may include a processing step A of patterning at least a portion of the conductive component (e.g., processing into a mesh) after the stacking step. In the processing step A, a patterned resist layer may be used as a mask to pattern at least a portion of the conductive component by etching at least a portion of the conductive component. The method in which the conductive component has a patterned portion in the stacking step may be as follows: the method for manufacturing a transparent antenna according to the fourth embodiment includes a stacking step in which the transparent resin layer in a stack having a transparent resin layer and a conductive component disposed on the transparent resin layer is located on a side closer to the supporting component than the conductive component, the transparent resin layer comprises at least one selected from the group consisting of the resin composition and its cured product according to the present embodiment, and the conductive component has a patterned portion.
[0108] When the laminated body according to the second embodiment includes the layer L, the method for producing a transparent antenna according to the fourth embodiment may include a processing step B of obtaining a patterned layer L (resist layer) by patterning at least a portion of the layer L after the lamination step and before the processing step A. In the processing step B, at least a portion of the layer L can be patterned by removing (developing) an unexposed portion (when the layer L has negative photosensitivity) or an exposed portion (when the layer L has positive photosensitivity), and after exposing the layer L, the unexposed portion or the exposed portion is removed (developed), thereby patterning at least a portion of the layer L. The method for producing a transparent antenna according to the fourth embodiment may include a step of exposing at least a portion of the layer L before the lamination step. As an embodiment using a laminate having a layer comprising at least one selected from the group consisting of a photosensitive composition and a cured product thereof, the following embodiment may be used: the method for manufacturing a transparent antenna involved in the fourth embodiment includes a lamination step of laminating the laminate on a supporting member in a state in which the first layer in the laminate having a first layer, a second layer, and a conductive member arranged between the first layer and the second layer is located closer to the supporting member than the second layer, the first layer comprises at least one selected from the group consisting of the resin composition involved in this embodiment and a cured product thereof, and the second layer comprises at least one selected from the group consisting of a photosensitive composition and a cured product thereof.
[0109] In the method for manufacturing a transparent antenna according to the fourth embodiment, the conductive component in the removal step A, the removal step B, and the lamination step may be a multilayer, or may include a first conductive component disposed on a transparent resin layer, and a second conductive component disposed on the first conductive component. At least one selected from the group consisting of the first conductive component and the second conductive component may be solid, or may include a patterned (e.g., mesh-like) portion. At least one selected from the group consisting of the first conductive component and the second conductive component may contain copper. When the conductive component includes the first conductive component and the second conductive component, in the lamination step, the transparent resin layer and the conductive component may be laminated on the supporting component in a state where the first conductive component is located closer to the supporting component than the second conductive component. The method for manufacturing a transparent antenna according to the fourth embodiment may include a removal step C of removing the second conductive component after the lamination step. In the removal step C, the second conductive component can be peeled off from the first conductive component. The method for manufacturing a transparent antenna according to the fourth embodiment may include a processing step of patterning (e.g., processing into a mesh) at least a portion of the first conductive component after the removal step C. In the processing step, for example, the first conductive member may be etched while a patterned resist layer is disposed on the first conductive member. The method for manufacturing a transparent antenna according to the fourth aspect may include a curing step of curing the transparent resin layer (resin composition of the transparent resin layer) to obtain a cured product (transparent substrate) before the removal step C, after the removal step C, or before and after the removal step C.
[0110] In the fifth aspect of the method for manufacturing a transparent antenna involved in the present embodiment, as a method for obtaining the transparent antenna involved in the first aspect, it is a method for manufacturing a transparent antenna using a laminate (the laminate involved in the second aspect) comprising the above-mentioned substrate film, the above-mentioned transparent resin layer (including at least one transparent resin layer selected from the group consisting of the resin composition involved in the present embodiment and its cured product), and the above-mentioned conductive component having a first conductive component and a second conductive component, and the manufacturing method comprises a removal step C of removing the second conductive component in a state where the transparent resin layer and the conductive component are stacked on the supporting component while the transparent resin layer in the laminate involved in the second aspect is located on the supporting component side relative to the conductive component.
[0111] The manufacturing method of the transparent antenna involved in the fifth embodiment may include a curing step of curing the transparent resin layer (resin composition of the transparent resin layer) to obtain a cured product (transparent substrate) in a state where the transparent resin layer and the conductive component are stacked on the supporting component before the removal step C, after the removal step C, or before and after the removal step C. In the curing step, the transparent resin layer may be cured in a state where the transparent resin layer and the conductive component are stacked on the supporting component while the transparent resin layer is located closer to the supporting component than the conductive component. The manufacturing method of the transparent antenna involved in the fifth embodiment may include a processing step of patterning (for example, processing into a mesh shape) at least a portion of the first conductive component after removing the second conductive component (after the removal step C). An example of a method for manufacturing a transparent antenna according to the fifth embodiment is a method for manufacturing a laminated body including the substrate film, the transparent resin layer (uncured transparent resin layer), and the conductive member having the first conductive member and the second conductive member as the laminated body according to the second embodiment, the manufacturing method comprising the removal step A (first removal step), a lamination step, a curing step, and a removal step C (second removal step). In the method for manufacturing a transparent antenna according to the fifth embodiment, at least one selected from the group consisting of the first conductive member and the second conductive member may contain copper. Furthermore, the first conductive member in the laminated body may be solid or may have a patterned (e.g., meshed) portion.
[0112] In the sixth aspect of the method for manufacturing a transparent antenna according to the present embodiment, as a method for obtaining the transparent antenna according to the first aspect, a removal step B is included in which a transparent resin layer (including at least one transparent resin layer selected from the group consisting of the resin composition according to the present embodiment and its cured product), a conductive component and a protective film are sequentially stacked on a supporting component to remove the protective film. In this case, the laminate may be, for example, a single-layer conductive component, and a demolding treatment is applied to at least a portion of one surface of the conductive component side of the protective film. The method for manufacturing a transparent antenna according to the sixth aspect may include: a removal step A of removing the substrate film in the laminate according to the second aspect before the removal step B; and a stacking step of stacking the transparent resin layer, the conductive component and the protective film on the supporting component. The method for manufacturing a transparent antenna according to the sixth aspect may include a curing step of curing the transparent resin layer (the resin composition of the transparent resin layer) before the removal step B, after the removal step B, or before and after the removal step B to obtain a cured product (transparent substrate).
[0113] The manufacturing method of the transparent antenna involved in the 1st to 6th embodiments may include a covering component forming step of forming a covering component (excluding the covering component of the resin composition and its cured product involved in this embodiment) on a conductive component, and may also include a step of configuring a protective component (such as a transparent component) on the covering component after the covering component forming step.
[0114] In the seventh aspect of the method for manufacturing the transparent antenna according to the present embodiment, as a method for obtaining the transparent antenna according to the second aspect, a covering component forming step is included in which a covering component including at least one selected from the group consisting of the resin composition according to the present embodiment and a cured product thereof is formed on a conductive component. In the covering component forming step, the covering component can be formed by supplying the resin composition according to the present embodiment to the conductive component, or the covering component (transparent resin layer) can be formed by disposing the transparent resin layer of the laminate according to the present embodiment on the conductive component. When the laminate according to the present embodiment is used, the transparent resin layer of the laminate according to the present embodiment can be disposed on the conductive component after removing the substrate film or the protective film. The step of forming a coating component can be a step of forming a coating component comprising at least one selected from the group consisting of the resin composition involved in the present embodiment and its cured product on a conductive component in a stack comprising a transparent resin layer (a transparent resin layer supporting a conductive component) and a conductive component arranged on the transparent resin layer. It can also be a step of forming a coating component comprising at least one selected from the group consisting of the resin composition involved in the present embodiment and its cured product on a transparent resin layer and a conductive component in a stack comprising a transparent resin layer (a transparent resin layer supporting a conductive component) and a conductive component arranged on a part of the transparent resin layer (for example, a part of the main surface of the transparent resin layer).
[0115] The manufacturing method of the transparent antenna involved in the 7th embodiment may include a curing step of curing the covering component (resin composition of the covering component) to obtain a cured product before the covering component forming step, after the covering component forming step, or before and after the covering component forming step. The manufacturing method of the transparent antenna involved in the 7th embodiment may include a curing step of curing the transparent resin layer (resin composition of the transparent resin layer) supporting the conductive component to obtain a cured product (transparent substrate) before the covering component forming step, after the covering component forming step, or before and after the covering component forming step. The covering component and the transparent resin layer supporting the conductive component may be cured in the same curing step. The manufacturing method of the transparent antenna involved in the 7th embodiment may include a step of disposing a protective component (e.g., a transparent component) on the covering component after the covering component forming step.
[0116] In an eighth aspect of the method for manufacturing a transparent antenna according to the present embodiment, as a method for obtaining the transparent antenna according to the second aspect, a lamination step is included in which a laminate having a conductive component and a covering component disposed on the conductive component is laminated on a transparent resin layer in a state where the conductive component in the laminate having a conductive component and a covering component disposed on the conductive component is located closer to the transparent resin layer than the covering component, and the covering component comprises at least one selected from the group consisting of the resin composition according to the present embodiment and a cured product thereof. As the laminate having a conductive component and a covering component disposed on the conductive component, the laminate according to the second aspect can be used, and in the lamination step, the transparent resin layer in the laminate according to the second aspect can be disposed as the covering component.
[0117] The manufacturing method of the transparent antenna involved in the 8th embodiment may include a curing step of curing the covering member (resin composition of the covering member) to obtain a cured product before the lamination process, after the lamination process, or before and after the lamination process. The manufacturing method of the transparent antenna involved in the 8th embodiment may include a curing step of curing the transparent resin layer (resin composition of the transparent resin layer) to obtain a cured product (transparent substrate) before the lamination process, after the lamination process, or before and after the lamination process. The covering member and the transparent resin layer may be cured in the same curing step. The manufacturing method of the transparent antenna involved in the 8th embodiment may include a step of configuring a protective member (such as a transparent member) on the covering member before the lamination process, after the lamination process, or before and after the lamination process.
[0118] In the manufacturing method of the transparent antenna involved in the seventh and eighth aspects, the transparent resin layer and the conductive component are the same as the transparent resin layer and the conductive component described above with respect to the laminated body and the transparent antenna involved in this embodiment. The transparent resin layer can be supported by the supporting component. In addition to the portion arranged on the conductive component, the covering component can also have a portion arranged on the transparent resin layer but not arranged on the conductive component, and can also abut against the transparent substrate and the conductive component.
[0119] In the manufacturing method of the transparent antenna involved in the above-mentioned 1st to 8th aspects, the above-mentioned steps, structures, etc. can be combined with each other for each aspect. For example, in the manufacturing method of the transparent antenna involved in the 5th aspect, the manufacturing method of the transparent antenna involved in the 4th aspect can use the above-mentioned steps, structures, etc.
[0120] The transparent antenna involved in this embodiment can be used in an image display device, a car component (windshield, rear window glass, sunroof, window, etc.), a building, etc. The image display device, car or building involved in this embodiment has the transparent antenna involved in this embodiment. The image display device can have an image display portion for displaying an image, and a frame portion (frame portion) located around the image display portion, and the transparent antenna can be arranged on the image display portion. The image display device can be used in various electronic devices such as personal computers, navigation systems (such as car navigation), mobile phones, clocks, electronic dictionaries, etc.
[0121] Figure 3 and Figure 4 It is a schematic cross-sectional view showing an example of an image display device, and shows a part of an image display portion of the image display device. Figure 3 The image display device 100 includes a transparent antenna 110 and a protective member 120 disposed on the transparent antenna 110. The transparent antenna 110 includes a transparent substrate 110a, a mesh conductive member 110b disposed on the transparent substrate 110a, and a covering member 110c disposed on the transparent substrate 110a and the conductive member 110b. Figure 4 The image display device 200 includes a transparent antenna 210 and a protective member 220 disposed on the transparent antenna 210. The transparent antenna 210 includes a transparent member 210a, a transparent substrate 210b disposed on the transparent member 210a, a mesh conductive member 210c disposed on the transparent substrate 210b, and a covering member 210d disposed on the transparent substrate 210b and the conductive member 210c. The covering members 110c and 210d cover the transparent substrates 110a and 210b and the conductive members 110b and 210c.
[0122] In the image display device 100, at least one selected from the group consisting of the transparent substrate 110a and the covering member 110c includes a cured product of the resin composition involved in the present embodiment, for example, it is formed by the cured product of the resin composition involved in the present embodiment. One of the transparent substrate 110a and the covering member 110c can be formed by a material having a total light transmittance of more than 90% per 100 μm thickness (for example, a polyolefin such as a cycloolefin polymer). In the image display device 200, at least one selected from the group consisting of the transparent substrate 210b and the covering member 210d includes a cured product of the resin composition involved in the present embodiment, for example, it is formed by the cured product of the resin composition involved in the present embodiment. One of the transparent substrate 210b and the covering member 210d can be formed by a material having a total light transmittance of more than 90% per 100 μm thickness. The conductive members 110b and 210c are formed, for example, of copper. The transparent member 210a is formed, for example, of polyolefin. The protective members 120 and 220 can be, for example, glass plates.
[0123] Example
[0124] Hereinafter, the present invention will be described in more detail using Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0125] <Preparation of resin varnish>
[0126] (Example 1)
[0127] While stirring, 80 parts by mass of elastomer 1 (maleic anhydride-modified styrene-butadiene-styrene block copolymer, manufactured by ASAHI KASEI CORPORATION, product name: Tuffprene 912, styrene content: 40% by mass), 20 parts by mass of polymerizable compound 1 (acrylic compound, 1,9-nonanediol diacrylate, manufactured by Showa Denko Materials Co., Ltd., product name: FA-129AS), 1.0 part by mass of polymerization initiator (2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane, manufactured by NOF CORPORATION, product name: Perhexa 25O) and 150 parts by mass of solvent (toluene) were mixed to obtain a resin varnish.
[0128] (Example 2)
[0129] A resin varnish was obtained in the same manner as in Example 1 except that the polymerizable compound 2 (methacrylic compound, 1,9-nonanediol dimethacrylate, manufactured by SHIN-NAKAMURA CHEMICAL CO., LTD., product name: NK ESTER NOD-N) was used instead of the polymerizable compound 1.
[0130] (Example 3)
[0131] A resin varnish was obtained in the same manner as in Example 1 except that the polymerizable compound 3 (methacrylic compound, 1,12-dodecanediol dimethacrylate, manufactured by SHIN-NAKAMURA CHEMICAL CO., LTD., product name: NK ESTER DDD) was used instead of the polymerizable compound 1.
[0132] (Examples 4 to 6)
[0133] A resin varnish was obtained in the same manner as in Examples 1 to 3 except that elastomer 2 (styrene-butadiene-styrene block copolymer, manufactured by ASAHI KASEI CORPORATION, product name: Asaflex 810, MFR (ISO 1133, 200°C, 5kgf) 5 g / 10 min, Vicat softening temperature (ISO 306, 10N, 50°C / h) 83°C) was used instead of elastomer 1.
[0134] (Examples 7 to 9)
[0135] A resin varnish was obtained in the same manner as in Examples 1 to 3 except that elastomer 3 (styrene-butadiene-styrene block copolymer, manufactured by ASAHI KASEI CORPORATION, product name: Asaflex 830, MFR (ISO 1133, 200°C, 5kgf) 6 g / 10 min, Vicat softening temperature (ISO 306, 10N, 50°C / h) 72°C) was used instead of elastomer 1.
[0136] (Examples 10 to 12)
[0137] A resin varnish was obtained in the same manner as in Examples 1 to 3 except that elastomer 4 (styrene-butadiene-styrene block copolymer, manufactured by ASAHI KASEI CORPORATION, product name: Asaflex 840, MFR (ISO 1133, 200°C, 5kgf) 7 g / 10 min, Vicat softening temperature (ISO 306, 10N, 50°C / h) 81°C) was used instead of elastomer 1.
[0138] (Comparative Example 1)
[0139] A resin varnish was obtained in the same manner as in Example 1 except that elastomer 5 (styrene-ethylene-butylene-styrene block copolymer, manufactured by ASAHI KASEI CORPORATION, product name: Tuftec H1041) was used instead of elastomer 1.
[0140] (Comparative Example 2)
[0141] A resin varnish was obtained in the same manner as in Example 1 except that elastomer 6 (hydrogenated styrene butadiene random copolymer, manufactured by JSR Corporation, product name: DYNARON 2324P) was used instead of elastomer 1 and the amount of the polymerization initiator used was changed to 0.2 parts by mass.
[0142] (Comparative Example 3)
[0143] A resin varnish was obtained in the same manner as in Comparative Example 2 except that the amount of the elastomer 6 used was changed to 60 parts by mass and 20 parts by mass of the polymerizable compound 1 was changed to 40 parts by mass of the polymerizable compound 2.
[0144] (Comparative Example 4)
[0145] A resin varnish was obtained in the same manner as in Comparative Example 2 except that the amount of elastomer 6 used was changed to 60 parts by mass and 20 parts by mass of polymerizable compound 1 was changed to 40 parts by mass of polymerizable compound 3.
[0146] <Evaluation of tensile elastic modulus and dielectric properties of cured products>
[0147] As a substrate film, a surface release-treated PET film (manufactured by FUJIMORI KOGYO CO., LTD., product name: HTA, thickness: 75 μm) was prepared. The above-mentioned resin varnish was applied to the release-treated surface of the PET film using a knife coater (manufactured by YASUI SEIKI CO., LTD., product name: SNC-300). Then, a resin film was formed by drying at 100° C. for 10 minutes in a dryer (manufactured by FUTABA KAGAKUIBARAKI CO., LTD., product name: MSO-80TPS). By adjusting the gap of the coater, the thickness of the dried resin film was adjusted to 100 μm. As a protective film, a surface release-treated PET film (manufactured by FUJIMORI KOGYO CO., LTD., product name: BD, thickness: 75 μm) was prepared, and then a laminated film A was obtained by attaching the release-treated surface of the protective film to the resin film.
[0148] The laminated film A was heat-treated at 120° C. for 30 minutes in a dryer (manufactured by FUTABA KAGAKU IBARAKI CO., LTD., product name: MSO-80TPS) to thermally cure the resin film, thereby obtaining an evaluation film having a base film, a cured film, and a protective film.
[0149] After cutting a laminate of 50 mm in length and 10 mm in width from the above-mentioned evaluation film, the base film and protective film of the laminate were removed to obtain a test piece. Under an environment of 25°C, the stress-strain curve of the test piece was measured using AUTOGRAPH (manufactured by Shimadzu Corporation, product name: EZ-S), and the tensile modulus was obtained from the stress-strain curve. The distance between the chucks during the measurement was set to 20 mm, and the tensile speed was set to 50 mm / min. As the tensile modulus, the value of the load between 0.5 N and 1.0 N was measured. The results are shown in Table 1.
[0150] From the above-mentioned evaluation films of Examples 1 to 12, a laminate with a length of 80 mm and a width of 80 mm was cut as a test piece, and then the relative dielectric constant (Dk) and dielectric loss tangent (Df) of the entire test piece were measured by the separated pillar dielectric resonator method (SPDR method) at 25°C using a vector network analyzer (manufactured by Agilent Technologies Japan, Ltd., product name: E8364B) and a 10 GHz resonator (manufactured by Kanto Electronics Application and Development, Inc., product name: CP531). In addition, after making a laminate (length: 80 mm, width: 80 mm) in which only the above-mentioned substrate film and protective film were laminated, the relative dielectric constant and dielectric loss tangent of the laminate were measured by the same method. The relative dielectric constant and dielectric loss tangent of the cured film were obtained by subtracting the measurement results of the above-mentioned laminate (laminate in which only the substrate film and protective film were laminated) from the measurement results of the above-mentioned test piece. Table 1 shows the results.
[0151] <Measurement of total light transmittance>
[0152] After cutting a laminate of 30 mm in length and 30 mm in width from the above-mentioned evaluation films of Examples 1 and 10, the base film and protective film of the laminate were removed to obtain a test piece. The total light transmittance (TT) of the test piece was measured using the method according to JIS K 7136. Specifically, a white LED light was irradiated under an environment of 25°C, and the total light transmittance of the light transmitted through the test piece was measured. SH7000 (product name) manufactured by NIPPON DENSHOKU INDUSTRIES Co., Ltd. was used as a measuring device. The total light transmittance was 91% in Example 1 and 90% in Example 10. By the same measurement, a total light transmittance of more than 90% was also obtained in Examples other than Examples 1 and 10.
[0153] <Evaluation of wrinkle appearance>
[0154] As a copper component, a laminate of copper foil A (thickness: 18 μm) and copper foil B (thickness: 2 μm) (Mitsui Mining & Smelting Co., Ltd., product name: MT-18FL) was prepared. After removing the protective film of the laminate film A, a pressurized vacuum laminator (Nikko-Materials Co., Ltd., product name: V130) was used to laminate the exposed resin film (resin film of the laminate film A) to the copper foil B of the copper component under the conditions of 0.5 MPa pressure, vacuuming for 10 seconds, and pressing for 30 seconds. After removing the substrate film (the substrate film of laminated film A), a pressurized vacuum laminator (manufactured by NIKKO-MATERIALS CO., LTD., product name: V130) was used to laminate the exposed resin film and the COP film (thickness: 100 μm) under the conditions of a pressure of 0.5 MPa, vacuuming for 10 seconds, and pressing for 30 seconds, thereby obtaining laminated film B.
[0155] The laminated film B was heat treated at 120° C. for 30 minutes in a dryer (manufactured by FUTABA KAGAKU IBARAKI CO., LTD., product name: MSO-80TPS) to thermally cure the resin film, thereby obtaining an evaluation film including a COP film, a cured film, copper foil B, and copper foil A.
[0156] A laminate of 100 mm in length and 100 mm in width was cut from the above evaluation film to obtain a test piece. Copper foil A was removed from the test piece, and the exposed copper foil B was checked for wrinkles. The case without wrinkles was evaluated as "A", and the case with wrinkles was evaluated as "B". The results are shown in Table 1.
[0157] [Table 1]
[0158]
[0159] Explanation of symbols
[0160] 10, 20, 30-laminate, 10a, 20a, 30a-base film, 10b, 20b, 30b-transparent resin layer, 10c-protective film, 20c, 30c, 30d, 110b, 210c-conductive component, 100, 200-image display device, 110, 210-transparent antenna, 110a, 210b-transparent base material, 110c, 210d-covering component, 120, 220-protective component, 210a-transparent component.
Claims
1. A resin composition comprising an elastomer, a polymerizable compound and a polymerization initiator, wherein: When the resin composition is heat-treated at 120° C. for 30 minutes, a cured product having a tensile elastic modulus of 50 MPa or more is provided.
2. The resin composition according to claim 1, wherein The elastomer comprises a styrenic block copolymer.
3. The resin composition according to claim 1, wherein The elastomer comprises a styrene-butadiene-styrene block copolymer.
4. The resin composition according to claim 1, wherein The content of the elastomer is 50% by mass or more based on the total mass of the resin composition.
5. The resin composition according to claim 1, wherein The polymerizable compound includes a (meth)acrylic compound.
6. The resin composition according to claim 1, wherein The polymerizable compound includes alkanediol di(meth)acrylate.
7. The resin composition according to claim 1, wherein The polymerizable compound includes a compound represented by the following general formula (I), In the formula, R 1 represents a group containing 9 or less carbon atoms and 2 or more oxygen atoms, R 2a and R 2b Each independently represents a hydrogen atom or a methyl group.
8. The resin composition according to claim 1, wherein The polymerization initiator comprises a peroxide.
9. The resin composition according to claim 1, wherein The polymerization initiator comprises a peroxy ester. 10 . A cured product, which is a cured product of the resin composition according to claim 1 .
11. A laminate comprising a base film and a transparent resin layer disposed on the base film, The transparent resin layer comprises at least one selected from the group consisting of the resin composition according to any one of claims 1 to 9 and a cured product thereof. 12 . The laminate according to claim 11 , further comprising a conductive member disposed on the transparent resin layer.
13. The laminate according to claim 12, wherein The conductive member contains copper.
14. The laminate according to claim 12, wherein The conductive member has a thickness of 5 μm or less.
15. A transparent antenna comprising a transparent substrate, a conductive component disposed on the transparent substrate, and a covering component disposed on the conductive component. At least one selected from the group consisting of the transparent substrate and the covering member comprises a cured product of the resin composition according to any one of claims 1 to 9.
16. The transparent antenna according to claim 15, wherein: The conductive member has a mesh portion.
17. The transparent antenna according to claim 15, wherein: The conductive member contains copper.
18. An image display device comprising the transparent antenna according to claim 15.
Citation Information
Patent Citations
Element for transparent antenna, and transparent antenna
JP2011091788A